Novel Natural-based Biomolecules Discovery for Tackling Chronic Diseases - Kwok, Hang Fai (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Natural-based biomolecules continuously play an important role in novel drug discovery for the treatment of chronic diseases. The development of natural peptide/protein-based, toxin-based, and antibody-based drugs can significantly improve the biomedical efficiency of disease-specific therapy. The focus of this Special Issue of Biomolecules will be on the most recent advances related to novel peptides/proteins, antibodies, and toxins as forms of medicinal therapy. Recent advances in the discovery and development of these natural biomolecules for use in targeted therapy and immunotherapy against chronic diseases (e.g., cancer, diabetes, cardiovascular diseases, and rheumatoid arthritis) will be addressed. The discussion on using novel disease-specific proteins/peptides/toxins/antibodies along with currently available FDA-approved drugs as combinatorial treatments will also be encouraged in this context. Finally, an overview of some of the selected promising natural biomolecules that are potentially able to address the forthcoming challenges in this field will be included. Both research (in particular) and review articles proposing novelties or overviews, respectively, are welcome.